EVALUASI STRUKTUR GEDUNG RSUD TANGERANG - Andhika Mega Laksary; Giovanni Putra Pratama; Himawan Indarto; Bambang Pardoyo (Jurnal Karya Teknik Sipil, 2013)
In the early design, RSUD Tangerang was built as 5 floor height building, but in the development process, it redesigned to add 3 more floors above the existing. Therefore, it needs a  re-analysis so the strength of the structure to resist the additional loads and earthquake load effect can be known. So the RSUD Tangerang Structure can be changed or reinforced.The result of the analysis is there are some columns that are not fulfilling the safety requirement due to temporary load combination (earthquake load effect). Therefore, it needs a retrofition, in this case it uses Jacketing Method, where this retrofition can strengthen and rigidify the structure. And for foundation, analysis can be done by ASD method.Concluded from ASD method  due to temporary load (earthquake load effect), foundation can not hold the vertical load so it needs a retrofition. From the analysis result, only the P3 pilecap with 3 piles that is not able to hold the vertical load. The retrofition that can be used is combining P3 and P3’ pilecaps.